Conceptual framework of social responsibility in the system of public administration - Kvasova, Valentyna (Public Administration and Regional Development, 2023)
The article carries out a comprehensive study, clarification and systematization of the conceptual foundations of social responsibility in the system of public administration. The evolution of the concept of "social responsibility" from the corporate sector to public administration is studied. The importance of incorporating social responsibility into public administration and its role in achieving sustainable development is highlighted. The author’s definition of the concept of "social responsibility in the public administration system" is proposed. The theoretical foundations of social responsibility in public administration are considered. Such theoretical approaches to social responsibility as ethical, economic, legal and others are presented. An integrated approach to social responsibility in public administration is considered. The relationship between social responsibility and sustainable development in the context of public administration is determined. It is explained that an integrated approach to social responsibility allows to harmonize the social, environmental and economic aspects of public administration. The advantages and challenges associated with the application of an integrated approach to social responsibility in public administration are presented. The role of stakeholders in the formation of social responsibility of public administration is considered. The classification of stakeholders in public administration is provided and their role in the formation of social responsibility and influence on the decision-making process is shown. The mechanisms for ensuring social responsibility in the public administration system are investigated. The tools for assessing and measuring social responsibility in public administration are presented, which help to assess the impact of the activities of public authorities on social aspects. The role of standards, regulations and recommendations in ensuring social responsibility, which act as regulators and determine the norms of behavior of public administration, is considered. The considered aspects of the development of the concept of "social responsibility", theoretical foundations, an integrated approach, the role of stakeholders and mechanisms for ensuring social responsibility allow us to understand the meaning and role of social responsibility in public administration.